Contruction of Desain GUI the Null Hypothesis Significante Testing (G-NHST) using Delphi XE8 - Muh. Rusmayadi; Darmasih Darmasih; Ahmad Nasrullah (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2018)
Students still use manual methods in processing their research data because they are unable to use and interpret the results of calculations from existing statistical test software such as SPSS, Minitab and others. So it is probable that a calculation error resulted in invalid results. Therefore, this study aims to develop a desktop-based quantitative research hypothesis test application using Delphi in combination with Microsoft Office (Ms. Access, Ms. Excell, and Ms. Word), which is communicative, easy to use, easy to distribute, small memory, and portable and dectop-based. This application development using 4-D development model developed by Thiangaran namely: Define, Design, Develop, and Disseminate